Soft Tissue Sarcoma of the Hand and Wrist: Epidemiology and Management Challenges - Nicholson, S.; Milner, R. H.; Ragbir, M. (Journal of Hand and Microsurgery, 2018)
Soft tissue sarcomas (STSs) of the hand and wrist are rare and confer a unique set of management challenges. We present a 15-year review and discussion of the epidemiology, tumor characteristics, treatment, and reconstructive strategies for such cases presenting to our regional sarcoma service. Three case examples are described. Of 218 STSs of the upper limb, 17 involved the hand or wrist. Alveolar rhabdomyosarcoma, synovial, and myxofibrosarcoma were the most common ones. Two patients required amputation for recurrence. Eight patients required flap reconstruction, of which five were free flaps with no failures or wound healing complications. Two-year overall survival rate was 92%. Local recurrence occurred in 12%. Limb-sparing surgery is possible in most patients, although there is often a degree of functional loss due to the surgical resection, and complex multistage reconstruction may be required. These lesions are still often incidental or unexpected findings when patients are treated for a presumed benign swelling. Clinicians treating localized swellings of the hand and wrist should maintain vigilance toward the possibility of a sarcoma diagnosis, to avoid delays in definitive treatment.
Keywords: soft tissue; sarcoma; hand; wrist; outcomes; management